A novel space intelligent computing and data processing architecture--the spacecraft payload health management unit (SPHMU) - Zhao, Wenjie; Rao, Jianing; Ma, Miao; Zhang, Jianzhe; Li, Shuanglong; Jia, Wenyuan; Dong, Zhenxing; Hou, Baocheng; Xue, Guofeng; Yin, Guodong; Zhu, Yan; An, Junshe (Frontiers in Astronomy and Space Sciences, 2025)
This paper primarily introduces a novel on-board intelligent computing and intelligent data processing architecture. This architecture leverages the collaborative work of high reliability computers (HRC) and high performance computers (HPC) to achieve highly reliable payload management and data interaction, as well as high-performance intelligent computing and data processing objectives in space application environments. This paper implements the novel on-board intelligent computing and intelligent data processing architecture using a combination of HRC and HPC. Specifically, HRC is responsible for data interaction with the spacecraft bus, including telemetry, telecommand, and control (TT&C) information of various payloads, as well as time and space information. HPC, on the other hand, primarily executes application software (APP) to process the received payload data. This includes computationally intensive tasks such as attitude and orbit determination. Communication between HRC and HPC is facilitated through a high reliability field programmable gate array (FPGA). This paper verifies the stability of this architecture through rigorous testing at the aerospace level. The novel on-board intelligent computing and intelligent data processing architecture possesses excellent computing capabilities, spatial adaptability, reliability, and a flexible structure, laying a foundation for high-performance computing in space.